Homeownership of immigrants in France - Laurent Gobillon; Matthieu Solignac (European Regional Science Association (ERSA), 2014)
We investigate the difference in homeownership rate between natives and immigrants as well as its evolution in France using a large longitudinal dataset over the 1975-1999 period. For people staying on the territory the whole time (ie. stayers), we show that returns of characteristics change in favor of immigrants consistently with better integration and this is particularly true for South Europeans. Moreover, for immigrants, entries on the territory have a large negative effect on the evolution of the homeownership rate. Although entrants have a better education than stayers, they are younger and thus at an earlier stage of the wealth accumulation process. They also locate in large cities where the homeownership rate is lower, and the returns of their characteristics are lower than the ones of stayers. Finally, exiters have a positive effect on the evolution of homeownership rate but this effect is only one third of the one of entrants.
Keywords: J15; R21; 330